1999
DOI: 10.1002/(sici)1521-3803(19990601)43:3<148::aid-food148>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the new millennium

Abstract: Beneficial effects on human health by specific probiotic microorganisms such as prevention of gastrointestinal tract infections immune stimulation, and balancing of the intestinal microflora have been established in numerous clinical trials. The successful probiotic strains which are mainly members of Lactobacillus and more recently Bifidobacterium naturally found in the human intestinal tract, have been traditionally incorporated into fermented milk products but have excellent potential for further inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…Intestinal mucin has been shown to inhibit the replication of rotavirus in vitro (3,29,35). Calves infected with rotavirus have been shown to have substantially less mucin covering the epithelium of the small intestine and colon than do healthy controls (34), but, as shown here, human infants, at least well-nourished infants, sustain the level of mucin during rotavirus diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal mucin has been shown to inhibit the replication of rotavirus in vitro (3,29,35). Calves infected with rotavirus have been shown to have substantially less mucin covering the epithelium of the small intestine and colon than do healthy controls (34), but, as shown here, human infants, at least well-nourished infants, sustain the level of mucin during rotavirus diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vitro evaluation of the adhesion to human intestinal mucus provides a suitable model for estimating the ability of probiotics to adhere to intestinal surfaces. It has been suggested that adhesion of lactobacilli to human intestinal mucus has a probiotic function in preventing the adhesion to and colonization of damaged tissue sites by invading pathogens (34). The induction of mucin gene expression is perhaps one of the mechanisms whereby probiotic strains minimize the interplay of other microbes with intestinal mucosal cells and thereby intestinal inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Other probiotic characteristics are inhibition of pathogens, modulation of metabolic activities and immunomodulation. Probably no probiotic strain has all these characteristics, but it is desirable that as many as possible should be present (Vaughan and Mollet, 1999;Gibson and Fuller, 2000;Mättö et al, 2006).…”
mentioning
confidence: 99%
“…bulgaricus, L. plantarum and L. acidophilus, heat-shock chaperones were found to be consistently upregulated presumably due to the need to repair acid-induced damaged proteins and/or to facilitate the folding of nascent proteins (Vaughan and Mollet, 1999;Somkuti and Steinberg, 1999;Van de Guchte et al, 2002). Although Lorca et al (2002) hypothesized that DnaK, DnaJ, GrpE, GroES and GroEL are important heat shock proteins found in L. acidophilus, little experimental evidence of the HSPs mechanism in this microorganismis established.…”
Section: Stress Responsesmentioning
confidence: 55%
“…Probiotics may also produce other substances (such as hydrogen peroxide and bacteriocins) that are inhibitory to potential enteric pathogens. Charteris et al 1998;Chandan, 2006;Vasiljevic and Shah, 2008 When the epithelial cells or normal microflora of the intestines become damaged or disturbed as a results of infection or irritation, altered gut permeability and inflammation may occur (Vaughan and Mollet, 1999). As mentioned above, probiotics have the potential to prevent and/or reduce infection associated with enteric pathogens.…”
Section: Probiotic Selection Criteria and Their Potential Health Benementioning
confidence: 99%